Relationship polymorphism exon 17 of insulin receptor (INSR) gene with polycystic ovarian syndrome among Malay ethnic in South Sumatera - Okta Emilia; Legiran; Safyudin; Syifa Alkaf (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2022)
Background: A sedentary lifestyle is a risk of obesity. One of the negative effects of obesity is insulin resistance. Insulin resistance is found in 50% - 90% of women with Polycystic Ovary Syndrome (PCOS).Objective: This study aimed to analyse the relationship polymorphism exon 17 of insulin receptor (INSR) gene in Malay ethnicity in South Sumatera.Methods: This is an observational analytic study with a case-control design conducted at the Molecular Biology Laboratory, Faculty of Medicine, Sriwijaya University. This study sample used blood taken from 80 people consisting of 40 cases and 40 controls. Genotyping and allotypic were performed using PCR-RFLP. Analysis was performed using SPSS 16.Results: The statistical analysis using the Chi-Square test on IMT resulting p-value = 0.003 (OR = 4.660 95% CI = 1.764 - 12.311). (Wild type) CC, (Mutant heterozygous) CT, (Homozygous Mutant) TT. The statistical analysis using the Pearson Chi-Square Genotype PCOS resulting p-value = 0.970 and fisher exact test on SOPK allotype resulting p-value = 0.500 (OR = 0.949 95% CI = 0.503 - 1,790).Conclusion: In conclusion, there was a significant relationship between BMI and PCOS among Malay ethnic in South Sumatera. There was no significant relationship between genotypic polymorphism and allotype exon 17 of INSR with PCOS in Malay ethnic groups in South Sumatera.